Driving results : six lessons learned from transforming an iconic company - Garfield, Gary A. (John Wiley & Sons, Inc., 2022)
"In 1988, Bridgestone Corporation, a Japanese company, paid billions to acquire the iconic but struggling Firestone Tire and Rubber Company. This acquisition was considered Bridgestone's last best chance to become a major tire player in the Americas. Firestone itself had been hampered by its own less-than-sterling reputation. Plagued by a large-scale tire recall (14 million + tires), a toxic corporate culture, and union issues, the acquisition wasn't an immediate success. In 2010, Gary Garfield was tapped to become the CEO of this new organization called Bridgestone Americas. With the help of a hand-picked leadership team and his 6-step approach to successfully drive change, Gary changed just about everything at Bridgestone Americas. With Gary at the helm and masterminding the company's overhauled corporate culture, Bridgestone Americas saw profits grow 500% overall during his tenure as CEO with record-breaking profits each year. Driving Results: Six Lessons Learned from Transforming An Iconic Company will breakdown the company's remarkable turnaround into the six key elements necessary to successfully drive change in any organization, department, or group: leadership, vision, culture, people, alignment and strategic focus. These six elements are compelling, yet understandable, manageable and doable in almost every context. They are based on real-world success by the people who actually made the changes happen at Bridgestone Americas"--